2009
DOI: 10.1111/j.1439-0523.2009.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interactions of heat stress disorder resistance in crisphead lettuce

Abstract: Lettuce is a cool season crop susceptible to physiological disorders when exposed to supra optimal temperatures. Genotype (G) by environment (E) interaction (GE) of rib discolouration, tipburn, premature bolting and ribbiness in crisphead lettuce was characterized under high temperature and long day growing conditions. Replicated data of 10 crisphead lettuce varieties from two plantings in each of four growing seasons at two locations in Quebec were analysed using the GGE biplot method. Head-weight-over-stem-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
4
33
1
Order By: Relevance
“…Tipburn leaves were associated with bolting only for red leaf lettuce, especially in the warmer E55 and P55 locations. The results indicated that the reduction in yield and the development of most of the physiological disorders in lettuce are associated with high temperatures as previously reported (Glenn, 1984;Jenni, 2005;Jenni and Yan, 2009;Ryder, 1999). There were significant variations in the susceptibility of lettuce genotypes to these physiological disorders and this susceptibility was also influenced by the interaction between the genotype and the environment (Jenni and Yan, 2009).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Tipburn leaves were associated with bolting only for red leaf lettuce, especially in the warmer E55 and P55 locations. The results indicated that the reduction in yield and the development of most of the physiological disorders in lettuce are associated with high temperatures as previously reported (Glenn, 1984;Jenni, 2005;Jenni and Yan, 2009;Ryder, 1999). There were significant variations in the susceptibility of lettuce genotypes to these physiological disorders and this susceptibility was also influenced by the interaction between the genotype and the environment (Jenni and Yan, 2009).…”
Section: Resultssupporting
confidence: 84%
“…Lettuce (Lactuca sativa L.) is a coolseason crop; it achieves optimum growth and development at an average temperature of 18°C. Production of lettuce at higher temperature ranges resulted in losses of yield and quality and led to some physiological disorders such as rib discoloration, tipburn, premature bolting, and ribbiness (Jenni, 2005;Jenni and Yan, 2009;Ryder, 1999). These physiological disorders were influenced by genotype, environment, and the interaction between the genotype and the environment (Jenni and Yan, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce (Lactuca sativa L.) is a cool season crop susceptible to physiological problems including tipburn, bolting, ribbiness, rib discoloration, and the development of loose, puffy heads when grown at supra-optimal temperatures [1]. At sub-optimal temperatures, growth can be slowed or plant death can occur.…”
Section: Introductionmentioning
confidence: 99%
“…In warm climate zones, such as the southeastern U.S., greenhouse lettuce production is often limited by occurrence of tipburn and premature bolting. Tipburn is a physiological disorder resulting from a calcium deficiency in young leaves [1,5], which is usually caused by high relative humidity and temperature [6], high light [7], and/or pH and water stress [8], not by a lack of calcium in the soil or nutrient solution [9]. Some of these factors, specifically high temperature and light, often lead to growth rates with which calcium translocation cannot keep pace [10].…”
Section: Introductionmentioning
confidence: 99%